Pengalaman Pasien Dirawat Inap di Rumah Sakit sebagai Upaya Penyusunan Strategi Pemasaran - Pamungkas, Fantri; Hariyanti, Tita; Prawestiningtyas, Eriko; Juhariah, Siti (Jurnal Aplikasi Manajemen, 2016)
An increasing number of hospitals in East Java during the past five years is 20%.Â This raises the tight competition. The hospital did the understanding of consumer behaviorÂ to the application of the concept of customer-oriented marketing. This study examines theÂ experiences of patients during care with phenomenological qualitative research methods toÂ obtain the meaning of the experience of patients during care. The result of the study showsÂ the choice of the hospital as a place for health care based on the patient's experience beforeÂ entering the hospital (patient feeling when declared sick, the search for treatment andÂ patient experience when going to the hospital). Moreover, a patient's view to the hospitalÂ consists of five P namely the place, price, people, product, and process. In the process ofÂ getting inpatient care in a hospital X, informants experience pleasant and unpleasant experiences.Â These experiences can be used to develop marketing strategies in the hospital X andÂ conduc in accordance with the change of the current condition of the hospital and theÂ hospital made plans in the future.